Academic dishonesty and ethical reasoning: Pharmacy and medical school students in New Zealand. (12th November 2012) - Henning, Marcus A.; Ram, Sanya; Malpas, Phillipa; Shulruf, Boaz; Kelly, Fiona; Hawken, Susan J.
Abstract : Background: There is ample evidence to suggest that academic dishonesty remains an area of concern and interest for academic and professional bodies. There is also burgeoning research in the area of moral reasoning and its relevance to the teaching of pharmacy and medicine. Aims: To explore the associations between self-reported incidence of academic dishonesty and ethical reasoning in a professional student body. Methods: Responses were elicited from 433 pharmacy and medicine students. A questionnaire eliciting responses about academic dishonesty (copying, cheating, and collusion) and their decisions regarding an ethical dilemma was distributed. Multivariate analysis procedures were conducted. Results: The findings suggested that copying and collusion may be linked to the way students make ethical decisions. Students more likely to suggest unlawful solutions to the ethical dilemma were more likely to disclose engagement in copying information and colluding with other students. Conclusions: These findings imply that students engaging in academic dishonesty may be using different ethical frameworks. Therefore, employing ethical dilemmas would likely create a useful learning framework for identifying students employing dishonest strategies when coping with their studies. Increasing understanding through dialog about engagement in academic honesty will likely construct positive learning outcomes in the university with implications for future practice.